Serum uric acid level in acute ischemic stroke in eastern India - Behera, Bijaya Kumar; Hui, Pankaj Kumar; Simethy, Roniya (International Journal of Research in Medical Sciences, 2017)
Background: Present study was done to estimate the level of serum uric acid in acute ischemic stroke and to find out whether it is protective against or increases the risk for ischemic stroke and its effect on stroke outcome. Methods: A total of 100 patients and 100 controls were taken randomly. Risk factors of stroke were considered such as hypertension, diabetes, adverse lipid profile, smoking and obesity. Serum uric acid level was measured in both cases and controls. Modified National Institute of Health (NIH) stroke scale score was calculated at the time of admission and discharge. Statistical analysis was done using SPSS 21.0 software. Results: Out of 100 patients studied 65 were males and 35 were females. The mean serum uric acid level in stroke cases was 6.11±1.47 where as it was 4.85±1.12 in controls. SUA levels was higher among males than females. The mean SUA in hypertensive subjects (6.58±1.33) was significantly higher than in normotensive subjects (5.23±1.42). There was statistically significant difference between SUA levels in diabetic (6.66±1.26) and non-diabetic patients (5.63±1.49). Mean SUA among overweight patients was (7.0±1.16) where as it was (5.22±1.23) in patients with normal weight. The mean SUA in smokers (6.33±1.38) was higher than that in non-smokers (6.02±1.51). There was significant positive correlation between SUA an NIH stroke scale score(P<0.05). SUA levels were significantly higher in patients who succumbed as compared to those who were discharged from hospital. Conclusions: SUA can be used as a marker for increased of stroke. Higher SUA is associated with a bad prognosis.